Multi-scale computational modeling for concrete damage by mixed pore pressures – case of coupled alkali–silica reaction and cyclic freeze/thaw. Issue 6 (15th October 2018) - Gong, Fuyuan; Takahashi, Yuya; Maekawa, Koichi
Abstract : Purpose: This paper aims to propose a multi-scale simulation approach for the concrete macro-mechanical damage caused by mixed micro-pore pressures, such as the coupled alkali–silica reaction (ASR) and freeze-thaw cycles (FTC). Design/methodology/approach: The micro-physical events are computationally modeled by considering the coupling effect between ASR gel and condensed water in the mixed pressure and motion. The pressures and transport of pore substances are also linked with the concrete matrix deformation at macro-scale through a poro-mechanical approach, and affect each other, reciprocally. Once the crack happens in the nonlinear analysis, both the micro-events (water and gel motion) and the macro mechanics will be mutually interacted. Finally, different sequences of combined ASR and FTC are simulated. Findings: The multi-chemo mechanistic computation can reproduce complex events in pore structures, and further the macro-damages. The results show that ASR can reduce the FTC expansion for non-air-entrained concrete, but may increase the frost damage for air-entrained concrete. The simulation is examined to bring about the observed phenomena. Originality/value: This paper numerically clarifies the strong linkage between macro-mechanical deformation and micro-chemo-physical events for concrete composites under coupled ASR and FTC.